Decision of self-promotion: theory and experiment - Wang, Xue (2024)
Given the importance of self-promotion in labour market, the decision-making process is not fully explored. This paper build the individual decision model for self-promotion, with the payoff from given payment rule setting payment based on self-reported value with adjustments, and the intrinsic preference of modesty and lying aversion which constraint the self-promotion. Intuitively, we found the negative relationship between self-promotion and marginal cost of modesty and lying, and possibility of underestimate when the marginal return of self-promotion from payment rule is too low. Based on the equilibrium, we found the fair payment rule which gives payment equal to agent's expected ability could take this underestimation into account. However, the presence of motivated belief which lead agent to be overconfident could result in more self-promotion and misperception of the fairness of the rule. To provide evidence for theoretical model, we plan to conduct a lab experiment with treatments of asking subjects to report signal or ability, introducing different rules in each treatment using strategy method, and elicit subject's belief and fairness perception at the same time.